Secret Agent Jack Stalwart. [book 5], The Secret of the Sacred Temple : Cambodia - Singer Hunt, Elizabeth (Red Fox, 2006)
The keeper of the sacred necklace of Angkor Wat has been kidnapped in the jungles of Cambodia. Can Secret Agent Jack Stalwart rescue her and prevent a madman from using the power of the necklace for his own wicked plans?